PENGARUH KOMPENSASI EKSEKUTIF, KONSERVATISME AKUNTANSI DAN FAMILY OWNERSHIP TERHADAP TAX AVOIDANCE: THE EFFECT OF EXECUTIVE COMPENSATION, ACCOUNTING CONSERVATISM, AND FAMILY OWNERSHIP ON TAX AVOIDANCE - Wijayanti, Etri; Ratnawati, Vince; Khoiriyah, Mayla; Nasir, Azwir (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This research is a quantitative study that aims to analyze and provide empirical evidence regarding the effect of executive compensation, accounting conservatism, and family ownership on tax avoidance in basic material sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. Tax avoidance is measured using the Cash Effective Tax Rate (CETR). In this study, the sample selection technique used purposive sampling with a sample of 33 companies obtained. This study uses secondary data obtained from annual reports. Data analysis was carried out using descriptive analysis, classical assumption test, linear regression analysis and hypothesis testing with analysis, namely statistical product and service solutions (SPSS) version 30.0. The results obtained from this study indicate that executive compensation and family ownership affect tax avoidance. However, accounting conservatism has no effect on tax avoidance. The implication of this research is that it is hoped that the government can provide a basis for designing more effective tax policies, increasing the transparency of tax reporting, and tightening supervision of companies with high risks in conducting tax avoidance, as well as for companies the importance of making better tax avoidance decisions, without harming the state, considering that tax avoidance can reduce state revenues.